Highly diastereoselective 1,3-dipolar cycloaddition of a D-galactose-derived nitrone with dimethyl maleate: synthesis of polyhydroxylated perhydroazaazulenes - Bande, Omprakash P.; Jadhav, Vrushali H.; Puranik, Vedavati G.; Dhavale, Dilip D. (Synlett, 2009)
An intermolecular 1,3-dipolar cycloaddition of a D-galactose-derived nitrone with dimethyl maleate was found to be perfectly diastereoselective at the nitrone carbon to give exclusive formation of isoxazolidine. The N-O bond reductive cleavage in isoxazolidine followed by lactam reduction afforded a pyrrolidine ring skeleton with sugar appendage that on acetonide cleavage and reductive amino-cyclization gave hitherto unknown hydroxymethyl-substituted hexa- and pentahydroxy perhydroazaazulenes.
Keywords: 1; 3-dipolar nitrone olefin cycloaddition (DNOC); diastereoselectivity; Iminosugars; inhibitors; nitrone

Stereo-controlled approach to pyrrolidine iminosugar C-glycosides and 1,4-dideoxy-1,4-imino-L-allitol using a D-mannose-derived cyclic nitrone - Bande, Omprakash P.; Jadhav, Vrushali H.; Puranik, Vedavati G.; Dhavale, Dilip D.; Lombardo, Marco (Tetrahedron Letters, 2009)
Intramolecular N-alkylation of 2,3-O-isopropylidene-5-O-methanesulfonyl-6-O-t-butyldimethylsilyl-D-mann ofuranose-oxime 7 afforded a five-membered cyclic nitrone 9, which on N-O bond reductive cleavage followed by deprotection of -OTBS and acetonide functionalities gave 1,4-dideoxy-1,4-imino-L-allitol (DIA) 3. Addition of allylmagnesium chloride to nitrone 9 afforded alpha-allylated product 10a in high diastereoselectivity providing an easy entry to N-hydroxy-C1-alpha-allyl-substituted pyrrolidine iminosugar 4a after removal of protecting group, while N-O bond reductive cleavage in 10a afforded C1-alpha-allyl-pyrrolidine iminosugar 4b. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cyclic nitrone; Enzyme inhibitors; Iminosugars; pyrrolidine

Synthesis and conformational study of chiral oxepines: the baylis-hillman reaction and RCM approach with sugar aldehyde - Jadhav, Vrushali H.; Bande, Omprakash P.; Pinjari, Rahul V.; Gejji, Shridhar P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2009)
The Baylis-Hillman reaction of 3-O-allyl-alpha-D-xylo-pentodialdo-1,4-furanose 3 afforded a diastereomeric mixture of D-gluco- and L-ido-configured alpha-methylene-beta-hydroxy esters 4a and 4b, respectively, in a ratio of 2:3. Reduction of the ester functionality in 4a/4b gave alcohols 5a/5b. The diene thus formed in 5a/5b was subjected to ring-closing metathesis (Grubbs' second-generation catalyst) to afford oxa-bicyclic ring system 6a/6b in high yield. Further manipulation of the aectonide functionality in 6a and 6b afforded new polyhydroxylated oxepines 1a/2a and 1b/2b, respectively. The (1)H NMR of oxepines 1a and 1b in D(2)O showed doubling of signals indicating their existence in two different rotamers/conformers. This fact was substantiated by calculating energetics of 1 and 2 conformers using the density functional theory and correlating the calculated (1)H NMR chemical shift pattern with that of the experimental spectra.

Synthesis of azepane and nojirimycin iminosugars: the sharpless asymmetric epoxidation of D-glucose-derived allyl alcohol and highly regioselective epoxide ring opening using sodium azide - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron-Asymmetry, 2010)
The Sharp less asymmetric epoxidation of D-glucose-derived ally! alcohol 4 afforded alpha- and beta-epoxides 5a and 5b in high stereoselectivity. The epoxide ring opening in 5a/5b was studied with different nucleophilic azido reagents, under various reaction conditions, and was found to be highly regioselective to give the preferential formation of 6-azido diol 6a/6b over 5-azido-diol 7a/7b. The 6-azido diol 6a/6b and 5-azido dial 7a/7b thus obtained were converted to the corresponding seven- and six-membered iminosugar, namely, azepane 1a/1b and 1-deoxy-nojirimycin 2a/2b. (C) 2010 Elsevier Ltd. All rights reserved.

Synthesis of eight-membered iminocyclitols from D-glucose - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2010)
The Baylis-Hillman reaction of 3-o-benzyl-alpha-d-xylo-pentodialdo-1,4-furanose 2 afforded a diastereomeric mixture of L-ido- and D-gluco-configurated alpha-methylene-beta-hydroxy esters 3a and 3b, respectively, in 1:1 ratio. Conjugate addition of benzyl amine on 3a gave adduct 4a as a major product while, addition of benzyl amine to 3b gave only one diastereomer 4b. Reduction of ester functionality in 4a/4b, opening of 1,2-acetonide functionality followed by reductive amino-cyclization under hydrogenation condition afforded azocanes 1c/1d in good yield. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Baylis-Hillman reaction; Conjugate addition; diastereoselectivity; Iminosugars